Anti-inflammatory Effect of Probiotic Limosilactobacillus reuteri KUB-AC5 Against Salmonella Infection in a Mouse Colitis Model - Buddhasiri, Songphon; Sukjoi, Chutikarn; Kaewsakhorn, Thattawan; Nambunmee, Kowit; Nakphaichit, Massalin; Nitisinprasert, Sunee; Thiennimitr, Parameth (Frontiers in microbiology, 2021)
Acute non-typhoidal salmonellosis (NTS) caused by Salmonella enterica Typhimurium (STM) is among the most prevalent of foodborne diseases. A global rising of antibiotic resistance strains of STM raises an urgent need for alternative methods to control this important pathogen. Major human food animals which harbor STM in their gut are cattle, swine, and poultry. Previous studies showed that the probiotic Limosilactobacillus ( Lactobacillus ) reuteri KUB-AC5 (AC5) exhibited anti- Salmonella activities in chicken by modulating gut microbiota and the immune response. However, the immunobiotic effect of AC5 in a mammalian host is still not known. Here, we investigated the anti- Salmonella and anti-inflammatory effects of AC5 on STM infection using a mouse colitis model. Three groups of C57BL/6 mice (prophylactic, therapeutic, and combined) were fed with 10 9 colony-forming units (cfu) AC5 daily for 7, 4, and 11 days, respectively. Then, the mice were challenged with STM compared to the untreated group. By using a specific primer pair, we found that AC5 can transiently colonize mouse gut (colon, cecum, and ileum). Interestingly, AC5 reduced STM gut proliferation and invasion together with attenuated gut inflammation and systemic dissemination in mice. The decreased STM numbers in mouse gut lumen, gut tissues, and spleen possibly came from longer AC5 feeding duration and/or the combinatorial (direct and indirect inhibitory) effect of AC5 on STM. However, AC5 attenuated inflammation (both in the gut and in the spleen) with no difference between these three approaches. This study demonstrated that AC5 confers both direct and indirect inhibitory effects on STM in the inflamed gut.